1995
DOI: 10.1007/s002770050096
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time of storage, temperature of storage, platelet number in platelet-rich plasma, packed cell, mean platelet volume, hemoglobin concentration, age, and sex on platelet aggregation test

Abstract: The influences of time of storage of platelet-rich plasma (PRP), temperature of storage of PRP, platelet number in PRP, mean platelet volume in whole blood, sex, age, hemoglobin concentration, and different forms of PRP storage on platelet aggregation (PAG) tests, performed with epinephrine, collagen, arachidonate, and ristocetin by a four-channel aggregation profiler (Platelet Aggregation Profiler, Model PAP-4, Bio/Data Corporation, Hatboro, PA 19040, U.S.A.), were evaluated in four groups of subjects (52 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Although the time span between withdrawal and analysis is of less importance, the measurement of labile blood components such as platelets should be performed within a reasonable time frame [18]. Storage temperature needs to be standardized because it modifies platelet reactivity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although the time span between withdrawal and analysis is of less importance, the measurement of labile blood components such as platelets should be performed within a reasonable time frame [18]. Storage temperature needs to be standardized because it modifies platelet reactivity [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the platelet aggregometry is the current "gold standard" test of platelet function [2]. MPV was not related to platelet aggregation, platelet function or platelet reactivity in current studies using platelet aggregometry [3][4][5]. In addition, Novara Atherosclerosis Study showed that MPV was not related to platelet reactivity and the prevalence and extent of coronary artery disease in diabetic patients.…”
Section: Dear Editormentioning
confidence: 92%
“…The PRP was separated from the SEC. The PRP was kept without packed cells at RT for no longer than 6 h. 22 Isolation, propagation, and identification of bone marrow-derived MSCs from rats Rat bone marrow-derived MSCs (BM-MSCs) were harvested from 12 2-to 4-month-old (200-250 g) male Wistar rats. The rats were killed after the administration of sodium pentobarbital intraperitoneally at a dose of 30 mg/kg.…”
Section: Preparation Of Prpmentioning
confidence: 99%